Capture vulnerability of sea turtles on recreational fishing piers. Issue 1 (21st December 2021) - Lamont, Margaret M.; Mollenhauer, Robert; Foley, Allen M.
Abstract: Capture vulnerability of commercial and recreational fishes has been associated with behavioral, morphological, and life‐history traits; however, relationships with non‐target species, such as sea turtles, have not been adequately studied. We examined species composition, timing of captures, morphological variables including body size and head width, and body condition of sea turtles captured from a recreational fishing pier in the northern Gulf of Mexico and of sea turtles captured in the waters adjacent to the pier. From 2014 to 2019, 148 net captures and 112 pier captures of three sea turtle species were documented. Green turtles were captured most frequently in the net and on the pier. Turtles captured from the pier were larger than those captured in the net. There was no difference in head width between net‐caught and pier‐caught turtles; however, small sample sizes limited those comparisons. The body condition index was lower for pier‐caught than net‐caught Kemp';s ridleys but did not differ with green turtles or loggerheads. Differences were also observed in the timing of capture on the pier as compared to in the net. Finally, the relationship between size, body condition, and pier‐capture vulnerability suggests these are complex interactions. Mortality of sea turtles captured from fishing piers could be selecting against bolder individuals, which may result in changes in sea turtle population demographics over a long time period. Abstract : We examined species composition, timing of captures, morphological variables including body size and head width, and body condition of sea turtles captured from a recreational fishing pier in the northern Gulf of Mexico and of sea turtles captured in the waters adjacent to the pier. Green turtles were captured most frequently in the net and on the pier. Turtles captured from the pier were larger than those captured in the net.